Standards-Based Leadership Preparation Program Involvement Through the Use of Portfolio Assessments - Donald G. Hackmann; Thomas L. Alsbury (Educational Considerations, 2005)
The school principal’s role has changed dramatically in the past few decades, moving away from management issues and into responsibilities related to leading school reform and facilitating student learning.